What is possible in women's economic empowerment at the research business interface: the story of innovation in agricultural systems in Indonesia - Cosijn, Michaela (Commonwealth Scientific and Industrial Research Organisation, 2019)
Presented by Michaela Cosijn (CSIRO), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.